LITERATURE REVIEW PRODUCTIVITY DETERMINATION: MOTIVATION, SKILL AND WORK ENVIRONMENT - Hazimi Bimaruci Hazrati Havidz; M. Rizky Mahaputra (Dinasti Publisher, 2021)
The article Literature Review Determination of Productivity: Motivation, Skills and Work Environment, aims to build hypotheses for further research. The methodology for writing this Literature Review article is Library Research which is sourced from the online application of Mendeley and Google Scholar. The results of this literature review article are: 1) Motivation has an effect on productivity; 2) Skills affect productivity; and 3) Work environment has an effect on productivity.